PREVALENCE AND CHEMOTHERAPY OF NEMATODES INFESTATION IN WILD AND DOMESTIC PIGEONS AND ITS EFFECTS ON VARIOUS BLOOD COMPONENTS - M.T. Basit; K. Pervez; M. Avais; I. Rabbani (Journal of Animal and Plant Sciences, 2006)
Prevalence and chemotherapy of nematodes infestation and its effect on various blood parameters was studied in pigeons. One hundred wild and domestic pigeons each were subjected to Coprological examination for the presence of nematodes eggs. From these naturally infested pigeons, forty wild and forty domestic pigeons were selected and divided into eight groups W1, W2, W3, D1, D2, D3, CW and CD each comprising 10 pigeons. Pigeons of groups W1, W2, W3 were treated with ivermectin, oxfendazole and piperazine, respectively. Similarly the pigeons of groups D1, D2, and D3 were treated with the same drugs whereas the pigeons of groups CW and CD were kept as untreated control. The overall prevalence of nematodes infestation was 57% whereas it was 60% and 55% in wild and domestic pigeons, respectively. The efficacy of ivermectin, oxfendazole, and piperazine in domestic pigeons was 100%, 60%, and 80%, respectively whereas it was 50%, 100% and 80% for oxfendazole, ivermectin and piperazine in wild pigeons, respectively. Treatment and control groups showed highly significant difference (p<0.05) in EPG, TLC, and haemoglobin estimation.
Keywords: Pigeons; Nematodes; Prevalence; Efficacy; Ivermectin; Oxfendazole; Piperazine